Choose your crop carefully - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A mushroom grower in Zimbabwe describes how, by growing a crop that is in high demand, he has made his job of marketing an easy one. He now has a large operation, producing over one ton of mushrooms per day, but the lessons about the value of identifying a niche crop, and paying close attention to growing conditions and packaging will also be relevant to small-scale farmers who grow, or would like to grow, delicate crops.